Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kinerja Pegawai Kantor Kecamatan Tanralili Kabupatean Maros - Pahmi Pahmi; Busman Busman (Jurnal Online Manajemen ELPEI, 2022)
This research was conducted at the Tanralili District Office, Kab. Maros at the end of October to the end of December. Sampling in this study used 34 respondents, the data collection technique is through a questionnaire distributed to respondents, while the research variables are job training (X), Employee Performance (Y). This research uses descriptive analysis with a quantitative approach, and to test the level of reliability using Cronbach Alpha and then the data is processed with Simple Linear Regression Analysis. Hypothesis testing using the t test with a significance level of 5%. This research uses SPSS Version 25 as a tool. From the results of simple linear regression analysis, it shows that employee performance is influenced by the HR competency variable. The result of determination (R2) uses an adjusted r square value, because it uses regression with one dependent variable. Namely equal to 0.007, which means that the Job Training variable is able to explain Employee Performance by 7.% while the remaining 93% is influenced by other variables that are not examined. From the results of the t test calculation, it can be seen that the HR competency variable partially has no effect on employee performance.